A performance comparison of DFIG using power transfer matrix and direct power control techniques - K. Viswanadha S Murthy; M. Kirankumar; G.R.K. Murthy (Institute of Advanced Engineering and Science, 2014)
This paper presents a direct power control and power transfer matrix model for a doubly-fed induction generator (DFIG) wind energy system (WES). Control of DFIG wind turbine system is traditionally based on either stator-flux-oriented or stator-voltage-oriented vector control. The performance of Direct Power Control (DPC) and Power transfer Matrix control for the same wind speed are studied. The Power transfer matrix Control gave better results. The validity and performance of the proposed modelling and control approaches are investigated using a study system consisting of a grid connected DFIG WES. The performance of DFIG with Power Transfer Matrix and Direct Power Control (DPC) techniques are obtained through simulation. The time domain simulation of the study system using MATLAB Simulink is carried out. The results obtained in the two cases are comparedDOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6150